PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS III SDIT AL-MADINAH CIBINONG BOGOR - Halfi Raodahtul Jannah; Santi Lisnawati; H. Sutisna (Jurnal Akrab Juara, 2019)
This study aims to 1) know the implementation of scramble learning models in civics subject in class III SDIT al-madina, 2) want to know student learning motivation in civics learning in class III SDIT al-madinah, 3) want to know whether using a scramble learning model can affect learning motivation in class III SDIT al-madinah civics subject. This study uses a quantitative method of quasi-experimental research with Randomized Two-Group Design research design in this study using two classes, namely the experimental class and the control class. The subjects of this study are SD III A and III F SDIT Al-Madinah which are chosen equal or the level of intelligence is equally. The instrument used to collect data is the learning motivation questionnaire. The research data were analyzed using SPSS 20 for Windows paired sample test and independent sample test. The results showed that the average value of students treated by using the scramble learning model was higher, the average experimental class was 52.28 while the control class was 41.45. Based on the calculation of the independent sample t test it shows that the number is greater than 0.05, the decision making is based on sig. (2-tailed) then Ha is accepted and Ho is rejected, it can be concluded that there is an effect of scramble learning model on student learning motivation in Civics subjects in class III SDIT Al-Madinah Cibinong Bogor.